Self-assessment of digital competence of doctoral students for conducting dissertation research - Symonenko, Svitlana; Симоненко, Світлана Вікторівна; Osadcha, Kateryna; Kruglyk, Vladyslav; Osadcha, Maryna (My University, 2025)
In the context of rapid digital transformation in higher education, digital competence has become essential fordoctoral students conducting dissertation research. This study explores the self-assessed digital competence of doctoral students in the context of dissertation research. Drawing on the DigComp 2.2 and DigCompEdu frameworks, the research instrument was adapted to reflect discipline-specific workflows and validated through expert review and pilot testing. A survey of 44 doctoral students from a Ukrainian university revealed moderate proficiency in information management and communication tools, alongside notable gaps in digital content creation and safety practices. While the study is limited by its institutional scope and reliance on self-assessment, the findings offer actionable insights for curriculum development and targeted support. Ethical approval was obtained, and participants provided informed consent. The study contributes to the discourse on digital transfor mation in postgraduate education and highlights the need for structured digital skill development aligned with research demands.
Keywords: doctoral students; digital competence; research; digital tools